ChemInform Abstract: Metal‐Free Synthesis of Substituted Pyridines from Aldehydes and NH4OAc under Air. Issue 15 (April 2015) - Yan, Rulong; Zhou, Xiaoqiang; Li, Ming; Li, Xiaoni; Kang, Xing; Liu, Xingxing; Huo, Xing; Huang, Guosheng
Abstract: Whereas substituted 2‐aryl propanals yield 3, 5‐diarylpyridines, substituted 3‐aryl propanals react to 3, 5‐diarylmethyl‐2‐(arylethyl)pyridines.